Spectral inclusions and stability results for strongly continuous semigroups - Abdelkader Elkoutri; Mohamed Aziz Taoudi (International Journal of Mathematics and Mathematical Sciences)
We prove some spectral inclusions for strongly continuous semigroups. Some stability results are also established.